1983
DOI: 10.1259/0007-1285-56-665-329
|View full text |Cite
|
Sign up to set email alerts
|

Exit dose studies in megavoltage photon therapy

Abstract: A coin-shaped ionisation chamber, orientated with its thin window facing away from the radiation source, was used to investigate the dose perturbations caused by the absence of back-scattering material near the exit surface of solid phantoms. Cobalt 60 and 4, 8 and 16 MV X-ray beams were used in the study. With no scattering material beyond the chamber window the ionisation was found to be as much as 17% less than the full scatter value. This was attributed to the absence of both back-scattered electrons and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…Since the fractional scatter contribution to depth dose is independent of the beam divergence, (32) we would expect the backscatter effect to be independent, as well. Our results confirmed that the BCF table was independent of SSD and the same was reported by Lambert et al (33) …”
Section: Discussionsupporting
confidence: 93%
“…Since the fractional scatter contribution to depth dose is independent of the beam divergence, (32) we would expect the backscatter effect to be independent, as well. Our results confirmed that the BCF table was independent of SSD and the same was reported by Lambert et al (33) …”
Section: Discussionsupporting
confidence: 93%
“…Consequently, R exit will be influenced by the obliquity of the exit surface (19). It has been found previously (16) that R exit decreases with increasing obliquity, and corrections have been made for this effect in the clinical studies reported here.…”
Section: Lack Of Full Electronic Equilibrium and The Effect Of Exit Smentioning
confidence: 63%
“…By pro vid ing accurate data ab ou t the volum e o f the radiation patients should receive during the treatm ent, and de tecting possible dosim etric errors p rior to the session, in vivo dosim eters prevent patients from taking less or m ore radiation than the planned doses (4). To ensure th a t patients undergo targe ted doses accurately and reliably, practitioners make use o f in vivo dosim etry systems.…”
Section: Introductionmentioning
confidence: 99%